Free Flaps for Advanced Oral Cancer in the “Older Old” and “Oldest Old”: A Retrospective Multi-Institutional Study - Grammatica, Alberto; Piazza, Cesare; Pellini, Raul; Montalto, Nausica; Lancini, Davide; Vural, Alperen; Barbara, Francesco; Ferrari, Marco; Nicolai, Piero (Frontiers in Oncology, 2019)
Introduction: Surgery followed by adjuvant therapy represents the most adequate treatment for advanced oral squamous cell carcinoma (OSCC). Free flaps are considered the best reconstructive option after major oral surgery. In the last decades, OSCC has increased in the elderly due to an augmented life span. The aim of this work is to evaluate the feasibility of microvascular surgery in patients older than 75 years, focusing on clinical and surgical prognosticators. Methods: “Older old” (aged ≥ 75) and “oldest old” (>85) patients who underwent microvascular reconstruction for OSCC from 2002 to 2018 were retrospectively evaluated in three referral Head and Neck Departments. Demographic, clinical, and surgical data were collected and analyzed. Pre-operative assessment was performed by ASA and ACE-27 scores. Complications were grouped as medical or surgical, and major or minor according to the Clavien-Dindo scale. Results: Eighty-four patients (72 “older old” and 12 “oldest old”) were treated with a free flap success rate of 94.1%. Thirty-seven (44.7%) and nine (10.7%) patients had minor and major medical complications, respectively; 18 (21.4%) and 17 (20.2%) had minor and major surgical complications, respectively. Twenty-one (25%) patients had both medical and surgical complications (with a statistically significant association, p = 0.018). Overall, 52 (61.9%) patients had at least one complication: ASA score, diabetes mellitus, and duration of general anesthesia (DGA) significantly impacted the complication rate at multivariate analysis. Conclusion: Our data confirm the feasibility of free flaps for OSCC reconstruction in appropriately selected elderly patients. Pre-operative assessment and aggressive management of glycemia in patients with diabetes is mandatory. DGA should be reduced as much as possible to prevent post-surgical complications. Comprehensive geriatric assessment is of paramount importance in this subset of patients.